BMT for Myelodysplastic Syndrome: When and Where and How - Jain, Akriti G.; Elmariah, Hany (Frontiers in Oncology, 2022)
Myelodysplastic syndromes (MDS) are a diverse group of hematological malignancies distinguished by a combination of ineffective erythropoiesis, along with a varied amount of dysplasia in the bone marrow, cytopenias and the risk of leukemic transformation. The hallmark of MDS is bone marrow failure which occurs due to selective growth of somatically mutated clonal hematopoietic stem cells. Multiple prognostic models have been developed over the years to help predict survival and leukemic transformation, including the international prognostic scoring system (IPSS), revised international prognostic scoring system (IPSS-R), WHO prognostic scoring system (WPSS) and MD Anderson prognostic scoring system (MDAPSS). Risk stratification, low risk (LR)-MDS or high risk (HR)-MDS along with transfusion requirements dictate the management of MDS. While the mainstay of management of patients with LR-MDS is improving quality of life and cytopenias, for patients with HR-MDS, delaying disease progression and improving survival is the cornerstone of treatment. The management of MDS, in this era, is highly individualized based on genetic and phenotypic make-up of the disease for each patient. Patients with low risk disease are treated with supportive care, erythropoiesis stimulating agents (ESAs), erythroid maturation agents (EMAs), immunomodulatory imide drugs (IMIDs) depending on disease status in the first line setting. However for high risk disease, the two treatment options that have shown survival benefit are hypomethylating agents (HMAs) and allogeneic stem cell transplant (alloSCT). AlloSCT is the only treatment that can offer cure for MDS and hence should be considered in the up-front setting for eligible patients. However, alloSCT is considered in less than 10% of MDS patients. Several patient related and disease related factors need to be considered when selecting suitable candidates for alloSCT. The timing of alloSCT is a crucial consideration since delaying transplant can lead to disease progression and earlier transplant can lead to higher morbidity and mortality. Multiple retrospective studies have shown that outcomes post alloSCT are significantly better in patients after attaining complete remission (CR). This review describes various factors that should be considered when choosing appropriate patients with MDS that should pursue transplant, timing of transplant, and outcomes of these patients.